Exploring the Fasciola hepatica kinome for the discovery of novel drug targets and drug candidates - Ajmera, Sagar; Justus Liebig University Giessen (My University, 2026)
Fasciolosis is a worldwide prevalent parasitic infection and considered a neglected tropical disease (NTD). It is caused by the liver flukes Fasciola hepatica and F. gigantica, which imposes considerable economic burdens and significantly affects both humans and animals. Parasites resistant to Triclabendazole (TCBZ), the predominant treatment for fasciolosis, have emerged on all continents, complicating the global management of fasciolosis, particularly in the absence of an effective vaccine. Protein kinases (PKs) are increasingly recognised as promising drug targets due to their crucial role in the survival and development of parasites, including the common liver fluke (F. hepatica). The cognisance of PKs in liver flukes remains scarce, with only a limited number of studies having explored PKs as potential therapeutic targets in this organism. An advanced and refined genomic-bioinformatic computational pipeline was employed to identify, curate, and classify a comprehensive kinome of the liver fluke, which accounted for 245 PKs and represented 2.14% of the liver fluke’s proteome. A comparative analysis with closely related trematode species and the human host revealed substantial orthology. Furthermore, the KEGG functional annotation indicated that 25% of the annotated PKs participate in conserved cancer-associated metabolic signalling pathways. This overlap emphasises the feasibility of a “drug repurposing” strategy, which was experimentally confirmed through the in vitro evaluation of approved small-molecule PK inhibitors. PK inhibitors associated with the PKs expressed in cells and tissues that are potentially crucial for parasite survival, including stem cells and muscle cells, were prioritised. The PKCβ inhibitor ruboxistaurin demonstrated lethal effects on both immature and adult liver flukes at a concentration of 50 μM, whereas the multi-RTK inhibitor vandetanib was lethal to immature liver flukes and significantly reduced the motility of adult liver flukes, indicating the efficacy of small-molecule PK inhibitors across different life stages of the liver fluke. Furthermore, these prioritised PK inhibitors demonstrated higher efficacy compared to TCBZ at equivalent concentration. Subsequently, a structure-based virtual screening of the prioritised FhPIM kinase using molecular docking was conducted. A managed chemical compound collection (MCCC) library, which consists of 85,000 compounds optimised for lead-likeness, was docked into the FhPIM kinase binding pocket. As a result, 34 novel compounds exhibiting high predicted binding affinity for the FhPIM kinase were identified. In the docking models, these ligands produced essential hydrogen-bonding networks within the conserved pharmacophores and effectively exploited the unique topology of the FhPIM kinase activation loop compared to the human PIM1 kinase, indicating significant potential for species-specific selectivity and reduced host toxicity. In the future, these 34 compounds will be subjected to in vitro evaluation to determine their capacity to inhibit the liver fluke vitality. Overall, this study identified and curated the kinome of the common liver fluke using in silico analyses; it demonstrated the potential for PKs as drug targets and identified active fasciolicidal compounds. Moreover, this study also provides evidence for the “drug-repurposing” of small-molecule PK inhibitors, which may represent an alternative intervention strategy in combating liver flukes. Additionally, the discovery of potential FhPIM kinase inhibitors derived from the MCCC library signifies a clear trajectory for the progression of target-based fasciolicidal strategies. Overall, this work establishes a solid basis for exploring future helminthic interventions based on PK inhibitors and for advancing basic research into the functions of PKs in the cell biology of liver flukes.
Kinom-Analysen des Leberegels Fasciola hepatica zur Identifizierung neuer Wirkstoffziele und Wirkstoffkandidaten
Keywords: ddc:570; ddc:610